Public Policy and Population Health: Why Is There So Little Public Policy Attention in Support of Health? - Raphael, Dennis (Canadian Review of Social Policy / Revue canadienne de politique sociale, 2007)
Intemational interest in the social determinants of heahh and their public policy antecedents is inqeasing. comparing with other weakhy nations, Canala presenl a mediocre population heabh profile cmd public policy enuironments increuingly less supportiorc of heabh. Howeuer, the cmadian public heabh gaze is firmly - and nmrowly - focused on hfestyle iswes ofadiet, physical actiotity cmd tobacco use. Reasctns for caneda’s neglect of structwal ancl public policy issaes are explored and Ten Ttps for Cana.dian Public Heahh Resectrchers andWorkers a-e presented. Lintdr€t mondial poru les ditermincn’tts sociaux de la sant6 et bs politiEtes qui s’y rat. nchent est grandissant. En compm’aison aorcc les autres pals rlches, le Cauda prasente m profil de smt6 midiocre et le soutien apf>ort6 par I’enuiromtement des politiques publiques ua en diminuant. Malgr6 cette situatioll, la santi publique canadienne pose wt regard fixe - et €toit - centrd xn les questions reliles au srylr de uie telles que l’alimentation, I’actiuit| physiq,Le et la consommatictn de tabac. Les raisons de kr n6gligence du Cawdt des questions de structlzres et de politiques publiques sont explor6es et " Dix con.seils poru bs cherchews et trauailbw’s en sant€ pubtique , sont pr€sentls.